Erratum: Assessing the Impact of Medical Treatment and Fumigation on the Superinfection of Malaria: A Study of Sensitivity Analysis - Bevina D. Handari; Dipo Aldila; Evllyn Tamalia; Sarbaz H.A. Khoshnaw; Muhammad Shahzad (The Indonesian Bio-Mathematical Society, 2025)
This erratum has been issued to correct an error in the Acknowledgement section of our previously published article (COMMUN. BIOMATH. SCI., VOL. 6, NO. 1, PP. 51-73, 2023). The research grant number was incorrectly stated due to a typographical mistake during manuscript preparation. The correct research grant number should read as indicated in this erratum. The authors apologize for this oversight and confirm that the correction does not affect the scientific content, results, or conclusions of the original article.